2020
DOI: 10.1186/s12920-020-00750-9
|View full text |Cite
|
Sign up to set email alerts
|

Weighted correlation network bioinformatics uncovers a key molecular biosignature driving the left-sided heart failure

Abstract: Background: Left-sided heart failure (HF) is documented as a key prognostic factor in HF. However, the relative molecular mechanisms underlying left-sided HF is unknown. The purpose of this study is to unearth significant modules, pivotal genes and candidate regulatory components governing the progression of left-sided HF by bioinformatical analysis. Methods: A total of 319 samples in GSE57345 dataset were used for weighted gene correlation network analysis (WGCNA). ClusterProfiler package in R was used to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Compared to previous studies, the functional modules and pathways identi ed by WGCNA method were also connected with speci c molecular subgroup of DCM [30][31][32]. We found that the speci c differential expression genes in subgroup 2 were mostly in the black, blue, green and grey WGCNA module.…”
Section: Discussionmentioning
confidence: 47%
“…Compared to previous studies, the functional modules and pathways identi ed by WGCNA method were also connected with speci c molecular subgroup of DCM [30][31][32]. We found that the speci c differential expression genes in subgroup 2 were mostly in the black, blue, green and grey WGCNA module.…”
Section: Discussionmentioning
confidence: 47%
“…Compared to previous studies, the functional modules and pathways identified by WGCNA method were also connected with specific molecular subgroup of DCM ( Zhou et al, 2020 ; Huang et al, 2021 ; Li et al, 2021 ). We found that the specific differential expression genes in subgroup 2 were mostly in the black, blue, green and grey WGCNA module.…”
Section: Discussionmentioning
confidence: 80%
“…HTRA1 has been identified as part of a candidate gene signature correlated with cardiomyopathies in a gene correlation network analysis model and its mRNA expression is upregulated 6.9 fold in DCM. 43, 44 PINK1 dependent phosphorylation of FAM65B attenuates ischemia reperfusion injury by suppressing autophagy. 45 The UNC45A gene has been characterized as potential de novo mosaic variant in sporadic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%